THE EXISTENCE OF FISH PROTEIN HYDROLYZATE OF LOMEK (Harpodon nehereus) PROCESSED BY USING PAPAIN ENZYME IN DIFFERENT HYDROLYZING TIME - Gita Amelia; Mirna Ilza; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe study was aimed to find out the proximate existenceoflomek(Harpodon nehereus)fish meal and fish protein hydrolyzate. It was also aimed to determine the optimum hydrolysis time and to get the profile of amino acid from the best the lomek fish protein hydrolyzate yielded. The research was using the experiment method to conduct the processing of lomek fish protein hydrolyzate by using papain enzyme in different hydrolysis time (for 5, 6, and 7 hours). The research was composed for non factorial completely randomized design. The results showed that the different hydrolysis time was affecting to the protein content, water content, ash content and fat content of fish protein hydrolyzate produced. The best fish protein hydrolyzate was yielded by hydrolising the fish meal for 7 hours, indicated by the highest protein content (86.03%), water content (27.39%), ash content (3.65%) and fat content (0.46%). There were 17 types of amino acids found in the fish protein hydrolizate, and consisting of essential and non-essential amino acids. The types of amino acids were dominatedby glutamic acid (1.01%), in the other hands, cysteine was showingthe lowest value (0.9 %).Keywords: fish protein hydrolyzate, lomek fish,papain enzyme